Corporate debt maturity and future firm performance volatility - Sato, Meg Adachi; Vithessonthi, Chaiporn * (Elsevier, 2018)
We propose a simple idea that corporate debt maturity should serve as a good indicator of future firm performance volatility. We show in a simple two-period model that the riskiness of corporate investment is a decreasing function of corporate debt maturity. If “observable” corporate debt maturity and ex ante “unobservable” corporate risk-taking is highly correlated, corporate debt maturity should be highly correlated with “ex post” realized firm performance volatility in following years. Using data on firms in 10 developing and developed countries during 1991−2013, we find that corporate debt maturity is negatively associated with future firm operating performance volatility but is not associated with future firm value volatility.